An Evaluation of the Implementation of the Equivalency Education Program in Community Learning Centers (CLCs) Bengkayang Regency - Agantina Venalia; Mami Hajaroh (FOUNDASIA, 2026)
This study aims to describe the results of evaluating the implementation of the equivalency education program at community learning centers. This is an evaluative study that utilizes the CIPP (Context, Input, Process, and Product) evaluation model. The research uses a descriptive qualitative approach and purposive sampling. The sample consists of two Community Learning Centers (CLCs) in Bengkayang Regency: The Adubs Community Learning Center and the Insan Madani Community Learning Center. The research subjects or data sources were the institution managers, tutors, and learners. Data was collected using observation, interviews, and documentation. Data analysis involved triangulation and three stages: data reduction, data presentation, and conclusion. The result showed: (1) from a contextual perspective, that implementers' understanding of non-formal education policies and standards is not yet fully optimal. The identification of learners' needs has not been effectively carried out on a regular basis, resulting in strategic planning that is not fully targeted. (2) From the input aspect, the implementation of the equity education program still has limitations in terms of human resource quality, infrastructure, and funding that do not meet standards; tutor qualifications are still not in line with regulations, and budget constraints hinder the effectiveness of achieving an ideal program. (3) Process aspect: program implementation is approaching compliance and effectiveness based on Ministry of Education and Culture Regulation No. 47 of 2023, but there are still weaknesses in management, institutional oversight, and supervision of teachers/institutional heads, which is rarely conducted. Partnerships at CLC Adubs are quite good, while at CLC Insan Madani, they are still limited, thereby reducing the program's reach and support. (4) The product aspect indicates that the program is effective, as evidenced by the learning outcomes of the learners, with a graduation rate of nearly 90%. This study recommends improving human resource quality, fulfilling infrastructure needs, strengthening management and supervision, and expanding partnerships to support the quality and sustainability of the equity education program.